UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MEMAHAMI UNSUR-UNSUR INTRINSIK CERPEN MELALUI METODE JIGSAW PADA SISWA SMPN 1 KOTA BOGOR - Dedi Husnaeni (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
Efforts to Improve Student Learning Outcomes in Understanding the Intrinsic Elements of Short Stories Through the Jigsaw Method in Bogor Junior High School StudentsÂ This study aims to identify and describe the increase in Literature Learning Outcomes in Understanding the Intrinsic Elements of Short Stories through the Jigsaw Method for Junior High School Students. The background problem is that students' ability to understand short stories is still not good. This problem can be reduced by using the Jigsaw method. This Classroom Action Research was conducted in two cycles by taking the setting at Junior High School Students (SMP Negeri 1) Bogor City class IX-E with a total of 37 students as a sample. The sample was given a test instrument listening to the reading of short stories in order to obtain an intrinsic element appreciation test score. The conclusion of this study is the average ability of students in Pre-Cycle 57. In Cycle I the level of achievement was still low with an average score of 71 and the number of students who completed 22 people so that the percentage of completeness only reached 71%. In Cycle II it was classified as good with an average score of 82 and the number of students who completed reached 28 people so that the percentage of completeness reached 87%. This proves that there is an increase in the ability to understand the intrinsic elements of short stories through the Jigsaw method. This means that the Jigsaw method is relatively effective in an effort to improve the ability to understand the intrinsic elements of short stories that are read to class IX-F students of Junior High School Students (SMP Negeri 1) Bogor City.